Switching Treatments in Clinically Stable Relapsing Remitting Multiple Sclerosis Patients Planning For Pregnancy - Lubna Almouzain; Fiona Stevenson; Declan Chard; Nur Faraheen Abdul Rahman; Fiona Hamilton (Sagepub, 2024)
BackgroundThe decision to have children can be complex, particularly for people with multiple sclerosis (MS). A key concern is the use of disease modifying drugs (DMDs) during pregnancy, and how continuing, stopping or switching them may affect the mother and child. In people with active MS, stopping medications puts the mother at risk of relapse and disease rebound. ObjectivesReview evidence on the effect of different switching strategies in people with stable relapsing remitting MS (RRMS). MethodsWe searched MEDLINE, EMBASE, EMCARE, CINAHL, SCOPUS, Cochrane Library up to March 2020. Only papers in English were included and no other limits were applied. Seven articles were included: four cohorts, two case reports and one randomized controlled trial (RCT). ResultsTwo strategies were found: de-escalating, which was associated with an increased risk of relapses, and switching between first line injectables, with no change in relapse rate observed. ConclusionEvidence on the effect of switching strategy on disease course in stable RRMS patients planning for pregnancy is scarce, but when switching, current evidence suggests the risk of relapses mirrors known medication efficacy.